Synthesis of Different Sizes TiO2 and Photovoltaic Performance in Dye-Sensitized Solar Cells - Mahmoud, Sawsan A.; Mohamed, Basma S.; Killa, H. M. (Frontiers in Materials, 2021)
In this work, the performance of dye sensitized solar cell contains different particle sizes was studied. TiO2 was prepared by sol-gel method with controlling the particle size through the addition of different H2O/Ti mole ratios = 0, 20, 30, and 40. The dried samples at 100 oC were characterized by x-ray diffraction, High resolution transmission electron microscope, dynamic light scattering, and surface area. The dynamic light scattering (DLS) results show that the size of TiO2 decreases as the H2O/Ti content increase from zero to 40. It was found that TiO2 nanoparticle with smaller particle size distribution has the lowest conversion efficiency of 0.95 % with H2O/Ti ratio = 40 while the photoelectrode with higher size has conversion efficiency of 1.59% for the water free sample. This is could be explained as the Larger particles have better dye adsorption, indicating that it has effective surface area for greater photon absorption and electron-hole generation. The results also indicate that trimodal distribution with larger size also absorbs different wavelengths due to the broad distribution of the particle size